2019
DOI: 10.1101/841221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Process Maintaining Glycerophospholipid Homeostasis in Mammalian Cells

Abstract: Glycerophospholipid (GPL) homeostasis in eukaryotic cells is thought to be maintained via biosynthesis, degradation and acyl chain remodeling. Here we provide evidence for an additional process termed "head-group remodeling" where other GPLs, when in excess, are rapidly converted to phosphatidylcholine and triacylglycerol. Mass spectrometric studies showed the formation of diacylglycerol, but not phosphatidic acid, from the exogenous GPL thus indicating that the first step is catalyzed by a phospholipase C-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Recently, we have shown that loading of any common GPL to HeLa, BHK-21, or CHO cells strongly inhibited the synthesis of the corresponding GPL class. 22,23 The GPL molecules in excess in a membrane should have an increased chemical activity, which should promote their binding to the active or a regulatory site of the synthetizing enzyme thus inhibiting its activity. Alternatively, the molecules in excess could, for example, in case of CTT, inhibit membrane association and thus the activity of the synthetizing enzyme.…”
Section: Chemical Activity Regulates Gpl Biosynthesismentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we have shown that loading of any common GPL to HeLa, BHK-21, or CHO cells strongly inhibited the synthesis of the corresponding GPL class. 22,23 The GPL molecules in excess in a membrane should have an increased chemical activity, which should promote their binding to the active or a regulatory site of the synthetizing enzyme thus inhibiting its activity. Alternatively, the molecules in excess could, for example, in case of CTT, inhibit membrane association and thus the activity of the synthetizing enzyme.…”
Section: Chemical Activity Regulates Gpl Biosynthesismentioning
confidence: 99%
“…Extensive knock-down studies indicated that different enzymes (including PLCs or similar enzymes) catalyze the initial, committed step of the interconversion or "head group remodeling". 23 Since loading of an exogenous GPL to the cells should greatly increase the chemical activity of the respective GPL class, it is most likely that chemical activity drives head group remodeling. A particular benefit of this novel homeostatic process is that it requires far less cellular energy than biosynthesis de novo, simply because the fatty acids need not to be activated to CoA derivatives.…”
Section: Chemical Activity Drives Gpl Glass Interconversion (Head Gmentioning
confidence: 99%
See 3 more Smart Citations